2015
DOI: 10.1155/2015/364710
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Regulatory T Cells in Vulnerable Atherosclerotic Lesions: Imbalance between Pro‐ and Anti‐Inflammatory Cells in Atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disease of the arterial wall in which presentation of autoantigens by dendritic cells (DCs) leads to the activation of T cells. Anti-inflammatory cells like Tregs counterbalance inflammation in atherogenesis. In our study, human carotid plaque specimens were classified as stable (14) and unstable (15) according to established morphological criteria. Vessel specimens (n = 12) without any signs of atherosclerosis were used as controls. Immunohistochemical staining was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 35 publications
(38 reference statements)
4
49
2
Order By: Relevance
“…However, the number and function of these cells decreases both in plaques and in circulation as disease progresses, consistent with a breakdown in tolerance and the appearance of proinflammatory T cells (9)(10)(11)(12). The Li study confirmed this decline in circulating Treg numbers alongside the expression levels of TGF-β and FoxP3 mRNA in PBMC from atherosclerotic patients, reflected in the serum by decreased TGF-β protein levels when measured by ELISA.…”
supporting
confidence: 52%
“…However, the number and function of these cells decreases both in plaques and in circulation as disease progresses, consistent with a breakdown in tolerance and the appearance of proinflammatory T cells (9)(10)(11)(12). The Li study confirmed this decline in circulating Treg numbers alongside the expression levels of TGF-β and FoxP3 mRNA in PBMC from atherosclerotic patients, reflected in the serum by decreased TGF-β protein levels when measured by ELISA.…”
supporting
confidence: 52%
“…T cells were then continuously present in later stages (fibroathermomas) of coronary arteries. Many studies have also detected T cells within carotid plaques (Kleindienst et al, ; Palma et al, ; de Boer et al, ; Chen et al, ; Erbel et al, ; Dietel et al, ; Rohm et al, ). Plaques of otherwise similar status in older patients contain higher levels of infiltrating T cells (Najib et al, ).…”
Section: Atherosclerosis and The Adaptive Immune System In Patientsmentioning
confidence: 99%
“…DC in human atherosclerotic lesions express CD83 and the content of CD83 + mature DC increased significantly in unstable plaques as compared to stable ones. 70, 71 CD83 regulates B cell activation and germinal center responses 72 as well as CD4 + T cell development. 73, 74 Although largely expressed by activated APCs, the costimulatory function of CD83 seems to be dispensable for murine T cell activation whilst CD83-stimulated human monocytes suppressed T cell responses.…”
Section: Co-stimulatory Pathways In Atherosclerosismentioning
confidence: 99%